CAR-T-ICI: Kombinasi chimeric antigen receptor T-cell dengan immune checkpoint inhibitor anti PD-1 selaku pilihan terapi terbaru kanker kolorektal: kombinasi chimeric antigen receptor T-cell dengan immune checkpoint inhibitor anti PD-1 selaku pilihan terapi terbaru kanker kolorektal - imam hermansyah; Eddy Zulfikar (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2021)
ABSTRACT Background: Colorectal cancer (CRC) as the third most common malignancy in the world is generally treated by surgery, radiotherapy, or chemotherapy based on the stage of the cancer. However, due to the invasive procedures and adverse reactions, scientists are developing treatment advancements with immunotherapy, especially Chimeric Antigen Receptor (CAR) T-cell which is considered more specific to tumor cells. However, the effectiveness of CART-T cells to treat solid tumors is still limited by Programmed Cell Death-1 (PD-1) through its immunosuppressive effect on T cells, hence the addition of anti PD-1 to CAR-T cells treatment is deemed necessary to increase its therapeutic potential. Objective: To discuss the potential of CAR-T cell in combination with anti PD-1 therapy for treatment of CRC. Method: The review materials used in this paper were taken from journals found through PubMed then compiled systematically. Results and Discussion: Based on previous studies, high level of IFN-? and TNF-? secretions were found in Epithelial Cell Adhesion Molecule (EpCAM) tumor cells, showing that EpCAM-CAR-T cells have specific cytotoxic effect on target tumor cells. The average colorectal tumor volume in the EpCAM-CAR-T cell group were lower than the control group, indicating that EpCAM-CAR-T cells were able to inhibit both the formation and growth of tumor cells. On the other hand, administration of anti PD-1, nivolumab for metastasis CRC shows a durable responses and disease control, as well as long-term survival. Conclusion: The combination of EpCAM-CAR-Tcell immunotherapy with anti PD-1 nivolumab could be an effective potential novel treatment for CRC. Keywords: anti PD-1, CAR-T cell, colorectal cancer, immunotherapy